Szenci Molnár Albert levelezése és a kora újkori barátságretorika - Laczházi, Gyula (Studia Litteraria, 2026)
In the study of Renaissance humanism, it has long been established that friendship played a crucial role in the self-organisation of humanists. Nevertheless, it is worth analysing Molnár Szenci’s diary and correspondence in the light of recent research into historically specific versions of early modern concepts of friendship. The paper approaches Szenci Molnár’s correspondence from the perspective of whether there are traces of more personal friendships in the letters, and whether there are differences in the rhetorical formulation of the letters that suggest a deeper emotional connection.